An Evaluation of White Matter Intensities in Patients with Pediatric Migraine - Burak Gülcen; Hilal Aydın; Erdoğan Bülbül; Bahar Yanik (Medicina)
Background and Objectives: This study aims to assess white matter hyperintensities (WMHs) in pediatric migraine patients and to elucidate the pathophysiology of the disease. Materials and Methods: A total of 30 patients diagnosed with migraine and 28 healthy individuals undergoing magnetic resonance imaging (MRI) scans for various reasons in our hospital between September 2019 and April 2023 were included in the study. We evaluated the presence, number, locations, and volumetric measurement of WMHs and the relationship between hyperintensity and attack profiles in migraine patients. Results: WMHs were observed at MRI in 18 (60%) of the 30 migraine patients and in 8 (28.6%) of the 28 controls. One hyperintense lesion was detected in nine members of the patient group, two in six patients, five in one patient, eight in one patient and nine in one. One hyperintense lesion was detected in eight healthy control group members. WMHs were significantly more common in the migraine patients than in the control group (p = 0.016). There was no significant relationship between hyperintensity in migraine patients and attack duration or frequency. Analysis also revealed no significant difference in terms of hyperintensity volumes (mm3) between the study group (19.73 ± 24.26) and the control group (5.62 ± 1.83). Conclusions: This study set out to show that migraine exerts neurological effects that are not solely limited to pain by emphasizing the pronounced differences observed on the brain MRIs of migraine patients. These findings may help us achieve a better understanding of the effects of migraine on cerebral structures and functions and identify therapeutic strategies in the future.